After the Anthropocene: Politics and geographic inquiry for a new epoch. (June 2014) - Johnson, Elizabeth; Morehouse, Harlan; Dalby, Simon; Lehman, Jessi; Nelson, Sara; Rowan, Rory; Wakefield, Stephanie; Yusoff, Kathryn
Crutzen and Stoermer's (2000) naming of the 'Anthropocene' has provoked lively debate across the physical and social sciences, but, while the term is gradually gaining acceptance as the signifier of the current geological epoch, it remains little more than a roughly defined place-holder for an era characterized by environmental and social uncertainty. The term invites deeper considerations of its meaning, significance, and consequences for thought and politics. For this Forum, we invited five scholars to reflect on how the Anthropocene poses challenges to the structures and habits of geography, politics, and their guiding concepts. The resulting essays piece together an agenda for geographic thought – and political engagement – in this emerging epoch. Collectively, they suggest that geography, as a discipline, is particularly well suited to address the conceptual challenges presented by the Anthropocene.